Huge primary scrotal lipoma: Case report and review of literature - Ibrahim Ballout; Rabih Awad; Bachar Al Ali; Linda Chamma; Hussein Issa; Mohamad Moussa (Urology Case Reports, 2023)
Primary scrotal lipomas are rare findings in urological practice. We present a case of a scrotal mass in a young patient, found to have a huge scrotal lipoma. He was diagnosed using imaging modalities and surgically managed with no further complications.